Renal involvement at diagnosis of pediatric acute lymphoblastic leukemia (2020)
Acute leukemia is the most common type of cancer in pediatric patients. This type of cancer accounts for a third of all childhood cancer cases. More than half of pediatric acute leukemia patients show signs and symptoms such as hepatomegaly, splenomegaly, pallor, fever and bruising at the time of diagnosis. In early stages of acute lymphoblastic leukemia (ALL), nephromegaly and other renal manifestations such as high blood pressure (HBP) and renal failure are uncommon, although renal infiltration and nephromegaly are common in advanced-stage pediatric patients. This is a retrospective case review with a critical appraisal of the existing evidence from the literature. We present a clinical case of a child with HBP associated with bilateral nephromegaly which resolved after chemotherapy treatment. This patient presented with HBP that required pharmacological treatment, likely owing to nephromegaly. All HBP secondary causes were rejected. Nephromegaly was resolved after chemotherapy treatment, and antihypertensive medication was discontinued. Nephromegaly and HBP are rare manifestations of ALL debut in pediatrics. The present case report illustrates this unusual combination and Suggests clinicians to consider malignancy as its causal factor, especially if the symptoms are accompanied by other suggestive extrarenal manifestations.